Annual World Bank Conference on Development Economics 2004 : Accelerating Development (Bangalore conference proceedings) - World Bank (Annual World Bank Conference on Development Economics, 2004)
The Annual Bank Conference on Development Economics (ABCDE) is one of the world's best known series of conferences for the presentation and discussion of new knowledge about development. First held at World Bank headquarters in Washington D.C. in 1988, the ABCDE has become broader in scope as the world's economies have become more interconnected and challenges have become more complex. Presenting the proceedings of the May 2003 World Bank Annual Bank Conference on Development Economics (ABCDE), the volume imparts new research findings and discussions on key policy issues related to poverty reduction by eminent scholars and practitioners from around the world. Topics include Fostering Entrepreneurship, Innovation and Growth; Challenges of Development in Lagging Regions; Participation, Inclusion and Results and Scaling Up and Evaluation. Contributors to the volume include, Nicholas Stern, Senior Vice President and Chief Economist of the World Bank; Azim Hasham Premji, Chairman of Bangalore's Wipro Corporation; Francois Bourguignon of the Ecole des Hautes Etudes en Sciences Sociales, Possiy, France; Partha Dasgupta of Cambridge University; Justin Lin of Hong Kong University; Rakesh Mohan, Deputy Governor of the Reserve Bank of India; Jean Philippe Platteau of the University of Namur, Belgium; Karen Polenske of the Massachusetts Institute of Technology; T. N. Srinivasan, of Yale University; and Anthony Venables of the London School of Economics. The Annual World Bank Conference on Development Economics 2004 is a critical reference guide for development research and will be of interest to practitioners and those studying international development and poverty reduction